Prognostic factors and patterns of failure after surgery for T4 rectal cancer in the beyond total mesorectal excision era. Issue 12 (24th July 2019) - Peacock, O.; Waters, P. S.; Bressel, M.; Lynch, A. C.; Wakeman, C.; Eglinton, T.; Koh, C. E.; Lee, P. J.; Austin, K. K.; Warrier, S. K.; Solomon, M. J.; Frizelle, F. A.; et al.
Abstract : Background: Despite advances in the rates of total mesorectal excision (TME) for rectal cancer surgery, decreased local recurrence rates and increased 5‐year survival, there still exists large variation in the quality of treatment received. Up to 30 per cent of rectal cancers are locally advanced at presentation and approximately 5–10 per cent still breach the mesorectal plane and invade adjacent structures despite neoadjuvant therapy. With the evolution of extended resections for rectal cancers beyond the TME plane, proponents advocate that these resections should be performed only in specialist centres. The aim was to assess the prognostic factors and patterns of failure after beyond TME surgery for T4 rectal cancers. Methods: Data were collected from prospective databases at three high‐volume institutions specializing in beyond TME surgery for T4 rectal cancers between 1990 and 2013. The primary outcome measures were overall survival, local recurrence and patterns of first failure. Results: Three hundred and sixty patients were identified. The negative resection margin (R0) rate was 82·8 per cent (298 patients) and the local recurrence rate was 12·5 per cent (45 patients). The type of surgical procedure (Hartmann's: hazard ratio (HR) 4·49, 95 per cent c.i. 1·99 to 10·14; P = 0·002) and lymphovascular invasion (HR 2·02, 1·08 to 3·77; P = 0·032) were independent predictors of local recurrence. The 5‐year overall survival rate for all patients was 61 (95 per cent c.i. 55 to 67) per cent. The 5‐year cumulative incidence of first failure was 8 per cent for local recurrence, 6 per cent for local and distant disease, and 18 per cent for distant disease. Conclusion: This study has demonstrated that a coordinated approach in specialist centres for beyond TME surgery can offer good oncological and long‐term survival in patients with T4 rectal cancers. Abstract : The aim was to assess the prognostic outcomes and patterns of failure after beyond total mesorectal excision (TME) surgery for T4 rectal cancers. A total of 360 patients from three specialist centres were evaluated; the negative resection margin was 82·8 per cent and the local recurrence rate was 12·5 per cent. This study demonstrates that a coordinated approach in specialist centres for beyond TME surgery can offer good oncological and long‐term survival in patients with T4 rectal cancers. RT, radiotherapy. Beyond TME improves outcome Abstract : Antecedentes: A pesar de las mejoras en los porcentajes de extirpación total del mesorrecto ( total mesorectal excision, TME) en la cirugía de cáncer de recto, la disminución de los porcentajes de recidiva local y el aumento de la supervivencia a 5 años, todavía existe una gran variabilidad en la calidad del tratamiento recibido. Hasta el 30% de los cánceres de recto están localmente avanzados en el momento del diagnóstico y aproximadamente el 5‐10% sobrepasarán el plano mesorrectal e invadirán las estructuras adyacentes a pesar del tratamiento neoadyuvante. Con la evolución de las resecciones ampliadas para los cánceres de recto que sobrepasan el plano de la TME, los defensores recomiendan que estas resecciones solo se realicen en centros especializados. El objetivo fue evaluar los factores pronósticos y los patrones de recidiva después de la cirugía ampliada más allá de la TME para los cánceres de recto T4. Métodos: Los datos se recogieron a partir de bases de datos prospectivas de tres instituciones de alto volumen especializadas en resecciones ampliadas más allá de la TME para el cáncer de recto T4 entre 1990 y 2013. Los criterios de valoración principal fueron la supervivencia global, la recidiva local y los patrones de la primera recidiva. Resultados: Se identificaron 360 pacientes. El margen de resección fue negativo (R0) en el 82, 8% ( n = 298) y el porcentaje de recidiva local fue de 12, 5% ( n = 45). El tipo de cirugía realizada (Hartmann: cociente de riesgos instantáneos, hazard ratio, HR 4, 49; i.c. del 95%: 1, 99‐10, 14; P = 0, 002) y la invasión linfovascular (HR 2, 02; i.c. del 95%: 1, 08‐3, 77; P = 0, 032) fueron factores predictivos independientes de recidiva local. La supervivencia global a 5 años para todos los pacientes fue del 61% (i.c. del 95%: 55‐67). La incidencia acumulada a los 5 años de la primera recidiva fue de 8% para la recidiva local, 6% para la recidiva local y a distancia, y 18% para la recidiva a distancia. Conclusión: Este estudio demuestra que un abordaje coordinado en centros especializados para cirugía más allá de la TME puede ofrecer una buena supervivencia oncológica y a largo plazo en pacientes con cáncer de recto T4.